2005
DOI: 10.1074/jbc.m500884200
|View full text |Cite
|
Sign up to set email alerts
|

p300/CBP-associated Factor Drives DEK into Interchromatin Granule Clusters

Abstract: DEK is a mammalian protein that has been implicated in the pathogenesis of autoimmune diseases and cancer, including acute myeloid leukemia, melanoma, glioblastoma, hepatocellular carcinoma, and bladder cancer. In addition, DEK appears to participate in multiple cellular processes, including transcriptional repression, mRNA processing, and chromatin remodeling. Sub-nuclear distribution of this protein, with the attendant functional ramifications, has remained a controversial topic. Here we report that DEK unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 66 publications
5
70
0
1
Order By: Relevance
“…Cells migrating to the lower chambers (ϳ10 6 ) collected from a 5-m-pore-size Transwell chemotaxis insert were washed three times with fluorescence-activated cell sorting (FACS) buffer (Dulbecco's PBS, 3% fetal bovine serum, and 0.09% NaN 3 ) and then incubated on ice with antibodies in 100 l of FACS buffer for 60 min. Cells were washed again three times in FACS buffer, fixed in 1 ml of PBS with 1% paraformaldehyde overnight at 4°C, washed three times with FACS buffer, and analyzed by EPICS XL Flow Cytometer System II software (Coulter, Miami, FL).…”
Section: Methodsmentioning
confidence: 99%
“…Cells migrating to the lower chambers (ϳ10 6 ) collected from a 5-m-pore-size Transwell chemotaxis insert were washed three times with fluorescence-activated cell sorting (FACS) buffer (Dulbecco's PBS, 3% fetal bovine serum, and 0.09% NaN 3 ) and then incubated on ice with antibodies in 100 l of FACS buffer for 60 min. Cells were washed again three times in FACS buffer, fixed in 1 ml of PBS with 1% paraformaldehyde overnight at 4°C, washed three times with FACS buffer, and analyzed by EPICS XL Flow Cytometer System II software (Coulter, Miami, FL).…”
Section: Methodsmentioning
confidence: 99%
“…20,[33][34][35][36][37] DEK is a highly modified protein, containing 57 potential phosphorylated sites and over 70 lysine residues with the potential to be poly ADPribosylated and ubiquitinated. 26,27,[38][39][40] Such modifications alter its ability to bind chromatin, re-localize, and carry out specific biological functions in a manner that remain poorly understood and have been studied primarily in cancer cells wherein DEK is over-expressed. 41 For example, DEK is phosphorylated by CK2 during interphase and phosphorylation levels appear to peak in G1.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike the HMGI(Y) proteins, association of DEK with these promoters results in repression of transcription, possibly in association with corepressors such as HDAC2 (25) and/or through the inhibition of p300/CBP and P/CAF HAT activity (49). Interestingly, it was recently shown that P/CAF acetylates DEK at lysine residues within the first 70 amino acids of DEK resulting in decreased affinity of DEK for DNA and its accumulation in IGCs (28). Since P/CAF is required for NF-B-dependent activation of transcription (7), it is possible that the recruitment of P/CAF to promoters by activated NF-B results in the subsequent acetylation of DEK and its dissociation from the promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The Absence of DEK Enhances P/CAF Recruitment to the Mcp-1 and IB␣ Promoters-Previously it was shown that P/CAF-mediated acetylation of DEK results in decreased affinity of DEK for DNA (28), indicating a functional interaction between P/CAF and DEK in transcriptional regulation. We performed ChIP assays to determine if the absence of DEK affected the recruitment of P/CAF to the Mcp-1 and IB␣ promoters.…”
Section: The Dekmentioning
confidence: 99%
See 1 more Smart Citation